ANALISIS KINERJA KEUANGAN PADA PT. TIRTA RAYA ABADI MEDAN - Syaharman, Syaharman (Bisnis-Net, 2018)
The purpose of this study is to determine the company's financial performance by looking at theinfluence of factors of acceptance and expenditure on financial performance This study sees theeffectiveness of managing and realizing budget revenue and expenditure PT. Tirta Raya AbadiMedan. Data used are primary and secondary data. The results showed that the performance of PT.Tirta Raya Abadi Medan see table and graph of financial performance development at PT. TirtaRaya Abadi Medan, the influence of revenue and expenditure in the management of corporate financehave a significant effect on the improvement and decrease in the graph of the performancedevelopment of PT. Tirta Raya Abadi Medan in the effectiveness of managing and realizing therevenue and expenditure budget, at least can know or make future policy design. In 2015 total assetsof the company reached 49% and in 2016 total assets of the company PT. Tirta Raya Abadi Medanreached 51%. This shows that the assets of PT. Tirta Raya Abadi Medan experienced a significantincrease so it can be said that the company's financial performance is good. In 2015 the company'stotal liabilities reach 68% and in 2016 total liability company PT. Tirta Raya Abadi Medan reached32%. This shows that the liability company PT. Tirta Raya Abadi Medan experienced a decrease inexpenditure so it can be said that the company's financial performance is good